2019
DOI: 10.1186/s12902-019-0444-6
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, diabetes and the risk of colorectal adenoma and cancer

Abstract: BackgroundColorectal cancer (CRC) is the fourth most commonly diagnosed gastrointestinal (GI) malignancy and the third leading cause of cancer-related death worldwide. In the current case-control study, an association between diagnosis of CRC, obesity and diabetes was investigated.MethodsDemographic characteristics, colonoscopy reports, history of drug, smoking, and medical history were collected from patients referred to a colonoscopy unit. The location, size and number of the polyps were recorded during the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 57 publications
3
45
1
3
Order By: Relevance
“…CRC is associated with a variety of factors. Representative factors include hypertension (42,43), folate (44,45), homocysteine (46), and diabetes milieus (47). Thus, treatment strategies and prognostic management methods change.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is associated with a variety of factors. Representative factors include hypertension (42,43), folate (44,45), homocysteine (46), and diabetes milieus (47). Thus, treatment strategies and prognostic management methods change.…”
Section: Discussionmentioning
confidence: 99%
“…20,38 The result also showed that obesity, smoking, and alcohol drinking were associated with an increased risk of early colorectal neoplasm, while regular moderate-to-intensity physical activity was a protective factor, consistent with previous findings. 39,[42][43][44][45] The proposed model was reliable and practical. On the one hand, the risk-based model could provide accurate information about the personal risks of colorectal neoplasm.…”
Section: Development Of the Risk Model And Assessmentmentioning
confidence: 81%
“…An increased risk was observed for DM patients being obese for a total duration of 4 years or more [163]. The occurrence of obesity measured based on body mass index (BMI) in the colorectal adenoma positive patient group was significantly higher than the control group [164]. A sedentary lifestyle, obesity, and a Westernized diet have been implicated in the etiology of both CRC and non-insulin-dependent DM [165].…”
Section: Discussionmentioning
confidence: 99%